2024
DOI: 10.1101/2024.05.09.593322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A conserved chronobiological complex timesC. elegansdevelopment

Rebecca K. Spangler,
Guinevere E. Ashley,
Kathrin Braun
et al.

Abstract: The mammalian PAS-domain protein PERIOD (PER) and itsC. elegansorthologue LIN-42 were proposed to constitute an evolutionary link between two distinct, circadian and developmental, timing systems. However, while the function of PER in animal circadian clocks is well understood molecularly and mechanistically, this is not true for LIN-42's function in timing rhythmic development. Here, using targeted deletions, we find that the LIN-42 PAS domains are dispensable for the protein's function in timing molts. Inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…These data were reminiscent of our work on NHR-23 as depletion of this factor causes aberrant aECM formation over the seam cells and nhr-23 activity also was necessary in the seam cells for developmental progression [32]. nhr-23 and lin-42 both regulate the molting timer and the heterochronic pathway and these two timers need to be tightly coordinated [27][28][29][30][31]36]. Pharmacologic uncoupling through nicotinic agonists results in animal death through rupturing when animals molt before seam cell division is completed [60].…”
Section: Mlt-11(rnai) Suppresses the Blister Phenotype Of Bli-4 Hypom...mentioning
confidence: 58%
See 1 more Smart Citation
“…These data were reminiscent of our work on NHR-23 as depletion of this factor causes aberrant aECM formation over the seam cells and nhr-23 activity also was necessary in the seam cells for developmental progression [32]. nhr-23 and lin-42 both regulate the molting timer and the heterochronic pathway and these two timers need to be tightly coordinated [27][28][29][30][31]36]. Pharmacologic uncoupling through nicotinic agonists results in animal death through rupturing when animals molt before seam cell division is completed [60].…”
Section: Mlt-11(rnai) Suppresses the Blister Phenotype Of Bli-4 Hypom...mentioning
confidence: 58%
“…A poorly understood genetic oscillator is thought to coordinate the expression of cuticle components and processing enzymes [25,26]. The molting cycle must also be tightly linked to developmental progression with homologs of circadian rhythm proteins (LIN-42/PER, NHR-23/ROR) playing important roles in both the molting and developmental timers [27][28][29][30][31][32][33][34][35][36]. Study of NHR-23-regulated genes revealed an enrichment in predicted protease and protease inhibitors [32,33].…”
Section: During Each Larval Stage Animalsmentioning
confidence: 99%